2016
DOI: 10.1080/19312458.2016.1150973
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Media Diet in a High-Choice Environment - Testing the List-Frequency Technique

Abstract: How to measure exposure to information in the media is highly disputed, primarily due to the difficulties of obtaining accurate self-reports. The growing supply of outlets and proliferation of information sources have added an additional level of complexity to these problems. Reflecting on old and new approaches for measuring exposure to political information, it is argued that both the specific source and the frequency of exposure must be taken into account. The validity of this so-called "list-frequency tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…The meta-regression analysis showed that adult respondents gave more reliable answers when asked about specific outlets rather than just "watching television". This finding supports current recommendations to ask about specific outlets (Andersen et al, 2016;, which is also a necessary precondition for linkage studies (Scharkow & Bachl, 2017) that combine media use and content measures on the outlet level. Regarding the response format, the meta-analytic results do not favor one version over the other for adult samples, but the open-ended hours/minutes option lead to less reliable answers among adolescents, in line with previous findings by (Coromina & Saris, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…The meta-regression analysis showed that adult respondents gave more reliable answers when asked about specific outlets rather than just "watching television". This finding supports current recommendations to ask about specific outlets (Andersen et al, 2016;, which is also a necessary precondition for linkage studies (Scharkow & Bachl, 2017) that combine media use and content measures on the outlet level. Regarding the response format, the meta-analytic results do not favor one version over the other for adult samples, but the open-ended hours/minutes option lead to less reliable answers among adolescents, in line with previous findings by (Coromina & Saris, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…This finding supports current recommendations to ask about specific outlets (Andersen et al, 2016;, which is also a necessary precondition for linkage studies (Scharkow & Bachl, 2017) that combine media use and content measures on the outlet level. Regarding the response format, the meta-analytic results do not favor one version over the other for adult samples, but the open-ended hours/minutes option lead to less reliable answers among adolescents, in line with previous findings by (Coromina & Saris, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…Even in the age of digital trace data and passive audience measurement, the workhorse of basically all communication research is self-report data. For several decades, scholars have investigated the reliability, accuracy and validity of self-reported media exposure measures (Allen, 1981;Chaffee & Schleuder, 1986), with most methodological research being conducted on question and response formats (Andersen, de Vreese, & Albaek, 2016;Coromina & Saris, 2009;Prior, 2013) or, more recently, on the accuracy and validity of self-reports compared to passive measures (LaCour & Vavreck, 2014;Prior, 2009; A previous version of this paper was presented at the 2016 annual meeting of the DGPuK methods division in Amsterdam, NL. I thank Marko Bachl for helpful comments and suggestions on the data analysis.…”
mentioning
confidence: 99%
“…Self-reports can also be optimized (or made less problematic): The American National Election study assesses days of week and type of medium (Althaus & Tewksbury, 2007). Even better is asking about specific news outlets (De Vreese & Semetko, 2004;Dilliplane, Goldman, & Mutz, 2013;Slater, 2004), preferably in combination with an assessment of frequency (Andersen, De Vreese, & Albaek, 2016). 2 This discussion is still ongoing and also touches on the ambition to include information processing variables and attention measures.…”
Section: Getting Specific I: What Survey Items/variables To Use?mentioning
confidence: 99%